Propionibacterium ruminifibrarum sp. nov., isolated from cow rumen fibrous content. Issue 8 (24th June 2019) - Vaidya, Jueeli D.; Hornung, Bastian V. H.; Smidt, Hauke; Edwards, Joan E.; Plugge, Caroline M.
Abstract : A novel propionate producing bacterium, strain JV5 T, was isolated from the rumen fibrous content of a Holstein Friesian dairy cow. Cells of strain JV5 T were Gram-stain-positive, non-motile and aerotolerant. Growth occurred between 35 and 45 °C, with an optimum at 39 °C. The pH range for growth was 6.5–8, with an optimum at pH 7. The 16S rRNA gene sequence of strain JV5 T was 98.4 and 96.5 % identical to those of Propionibacterium australiense DSM 15818 T and Propionibacterium acidifaciens DSM 21887 T, respectively. Genome wide average nucleotide identity and digital DNA–DNA hybridization values were 88.3 and 35.5 %, respectively, against P. australiense DSM 15818 T . The G+C content of strain JV5 T was 68.9  mol%. Strain JV5 T did not produce urease and was able to metabolize glutamate, but not aspartate and glycine. Strain JV5 T was able to ferment a range of substrates including certain simple and complex carbohydrates, sugar alcohols and amino acids. Chemotaxonomic analysis of strain JV5 T revealed the presence of meso- diamino pimelic acid isomers similar those found in P. australiense, but different from P. acidifaciens . The observed major (>10 %) cellular fatty acids in strain JV5 T (C18 : 1  ω9 c, anteiso-C15 : 1, C16 : 0, C17 : 0 and C16 : 0 alcohol) were also different from those observed in P. australiense and P. acidifaciens . Based on these findings, a novel species is proposed within the genus Propionibacterium, Propionibacterium ruminifibrarum sp. nov. (type strain JV5 T =DSM 106771 T =TISTR 2629 T ).